An abnormal two-way shape memory effect in a rapidly solidified Ni51Ti49 alloy induced by low temperature constrained aging. (May 2018) - Li, Y.Y.; Yao, X.Y.; Cao, S.; Ma, X.; Zeng, C.Y.; Zhang, X.P.
Abstract: An abnormal two-way shape memory effect (TWSME) is found in a rapidly solidified Ni51 Ti49 alloy strip undergoing constrained aging treatment at relatively low temperatures (e.g., approximately below 385 °C for aging time of 1 h), which embodies the bending of the strip toward constrained position during martensitic transformation on cooling, showing stark difference from normal TWSME. The abnormal TWSME of the alloy is caused by weaker coherent stress field produced by ultrafine nano-sized Ni4 Ti3 precipitates than the residual stress field, whereas the latter dominates martensitic transformation and leads to bending with the direction opposite to that of normal TWSME. Graphical abstract: Unlabelled Image